Spain, Split and Talk: Quantifying Regional Independence - Hanna Adam; Mario Larch; Jordi Paniagua (Center for Economic Studies and ifo Institute (CESifo), 2023)
We quantify the economic impact of a potential secession of Catalonia from Spain. Using a novel dataset of trade flows between 17 Spanish sub-national regions and 142 countries, we estimate effects of different levels of borders on trade flows and uncover heterogeneity in country-to-country, region-to-country, region-to-region, as well as EU border effects. We use a general equilibrium analysis to understand the consequences of a potential Catalan secession, considering the associated political uncertainty. In counterfactual experiments, we impose new borders on Catalan trade, potentially within or outside the EU, resulting in a welfare decline for Catalonia and the remaining Spanish regions.
Keywords: F10; F13; F14; H77; R12; 330; international trade; regional trade; border effects; regional independence